Interviewing Therapists About Working With Sexual Assault Survivors: Researcher and Therapist Perspectives - Ullman, Sarah E. (Violence against women, 2014)
This article provides an account of the author’s experience interviewing clinicians about their work with sexual assault survivors and clinicians’ experiences working with this population. Twelve clinicians who worked with sexual assault survivors practicing in a range of professional settings completed semi-structured face-to-face interviews. Grounded theory and open-coding analyses were conducted on the researcher’s log, case summaries, and verbatim-transcribed interview transcripts to uncover themes regarding (a) the researcher’s experience of the interviewees and (b) the therapists’ reports of their experiences working with survivors. Conclusions are drawn for researchers conducting interviews with therapists and clinicians working with sexual assault survivors.